ANALISIS PENGARUH PEMBIAYAAN MURABAHAH, MUSYARAKAH, DAN QARDH TERHADAP PROFITABILITAS BANK BTPN SYARIAH PERIODE 2019-2023 - Ramadhan, Aditya (Islamic Economics and finance in Focus, 2023)
This study discuss the impact of Murabahah, Musyarakah, and Qardh Financing on Profitability (ROA) at Bank BTPN Syariah for the 2019-2023 period. The research method used is a quantitative method using secondary data, with a total sample of 46 samples. The data collection technique is by documentation from the financial reports of PT Bank BTPN Syariah which are published on the OJK website and the Bank BTPN Syariah website. Data analysis techniques used classical assumption testing, hypothesis testing, and multiple linear regression with the SPSS version 26 application to process the data. The results of the analysis of this study indicate that murabahah financing has a significant positive effect on profitability. Musyarakah financing is proven to have a significant negative effect on profitability. Qardh financing is proven to have a significant negative effect on profitability.